Analysis of Monopoly Risk in TikTok Shop's Acquisition of Tokopedia: A Per Se Illegal Perspective - Abdullah Taufik (Khazanah Hukum, 2025)
A company's strategy to accelerate marketing reach and introduce new businesses to consumers can be implemented through a stock acquisition scheme, as demonstrated by TikTok's acquisition of 75% of Tokopedia's shares. However, excessive stock ownership dominance has the potential to lead to control over production and the goods and services market, which may trigger monopolistic practices that harm the public interest. This study aims to analyze potential violations of business competition law related to e-commerce market dominance resulting from the acquisition of the TikTok Shop digital platform business over Tokopedia. The research method used is normative juridical, with a legal and regulatory approach related to acquisitions and anti-monopoly laws, as well as a case study approach to relevant regulations. The findings of this study indicate that the acquisition of TikTok Shop over Tokopedia, along with the trade policies implemented, has a strong potential to result in monopolistic practices based on the per se illegal approach.